Experimental study on jatrophapalm diesel blends as alternative fuels - Kalam, M.A.; Masjuki, Haji Hassan; Liaquat, A.M.; Jayed, M.H.; Nurul, F.M. (2010)
This paper presents experimental results carried out to evaluate fuel consumption, exhaust gas temperature and the emissions characteristics of jatropha-palm diesel blends in an internal combustion engine. A total of two fuel samples such as (i) 100% diesel fuel (D100) and (ii) 5% jatropha and 5% palm diesel (methyl ester of palm oil) with 90% diesel fuel (J5P5) were used. The D100 was used for comparison purposes. The details physicochemical properties of J5P5 has been measured and compared with D100 fuel. The emission parameters measured are carbon monoxide (CO), carbon dioxide (CO2), hydrocarbon (HC), smoke and oxides of nitrogen (NOx). The emissions were measured using two exhaust gas analyzers namely, Bacharach and Bosch gas analyzers. A single cylinder engine - dynamometer test bed was used to conduct this test. The test conducted with a constant engine rpm of 2000 for various brake mean effective pressures. The test results show that the combination palm diesel (methyl ester of palm oil) and jatropha (as non edible oils) blend gives prominent results through reducing emissions. Along the emission and physicochemical properties, fuel consumption and exhaust gas teperature results have also been presented with details discussion.